2015
DOI: 10.3389/fbioe.2015.00049
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Structure of Photosynthetic Microbial Biofuels for Improved Engine Combustion and Emissions Characteristics

Abstract: The metabolic engineering of photosynthetic microbes for production of novel hydrocarbons presents an opportunity for development of advanced designer biofuels. These can be significantly more sustainable, throughout the production-to-consumption lifecycle, than the fossil fuels and crop-based biofuels they might replace. Current biofuels, such as bioethanol and fatty acid methyl esters, have been developed primarily as drop-in replacements for existing fossil fuels, based on their physical properties and auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Under extreme environmental conditions, microalgae synthesize and produce various secondary metabolites to retain their growth rate. In general, lipids act as an energy-rich carbon storage battery that enables the cells to survive under transient harsh environmental conditions (Hellier et al, 2015). A number of studies showed that stress conditions increased levels of intracellular reactive oxygen species (ROS), which in turn changed the carbon metabolic flux from glycolysis to the oxidative pentose phosphate pathway and subsequently resulted in the excessive accumulation of intracellular equivalents of excessive reduction, such as NADPH (Hu et al, 2008;Shi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Under extreme environmental conditions, microalgae synthesize and produce various secondary metabolites to retain their growth rate. In general, lipids act as an energy-rich carbon storage battery that enables the cells to survive under transient harsh environmental conditions (Hellier et al, 2015). A number of studies showed that stress conditions increased levels of intracellular reactive oxygen species (ROS), which in turn changed the carbon metabolic flux from glycolysis to the oxidative pentose phosphate pathway and subsequently resulted in the excessive accumulation of intracellular equivalents of excessive reduction, such as NADPH (Hu et al, 2008;Shi et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…An engineered Synechocystis PCC 6803 strain overexpressing RuBisCO, encoded by RuBisCo gene operon (rbcLXS), exhibited increased RuBisCO activity, growth rate and biomass 7 . Not only the carbon source but also many carbon intermediates are produced within the CBB cycle and indirectly flow to other crucial metabolic processes; for example, the conversion of the intermediate 3-phosphoglycerate (3-PG) to pyruvate and subsequently to acetyl-CoA, which are used in central metabolic pathways 8 . Moreover, dihydroxyacetone phosphate (DHAP) which is one of intermediates in the CBB cycle can be converted to glycerol-3-phosphate (Gro3P) catalysed by glycerol-3-phosphate dehydrogenase (GPD encoded by glpD gene) 6 , which is further partly used as a glycerol backbone for lipid molecules.…”
mentioning
confidence: 99%
“…Although much focus has been placed on the identification of non-edible feedstocks for the production of biodiesel, 17 a wide range of chemical and biological processes are currently under study with potential for the production of fuel molecules suitable for compression ignition combustion. Alkanes, alkenes, alcohols, methane and hydrogen can be produced from genetically modified micro-organisms including photosynthetic micro-algae, [18][19][20][21] whereas catalytic upgrading of fermentation products can result in higher-weight alcohols and ketones. 22,23 Many methods of combined thermal, chemical and biological treatment of lignocellulosic biomass can produce ketones, short-chain fatty acid esters, acids, furans, methane and phenols.…”
Section: Introductionmentioning
confidence: 99%